The Role of Social Media as a Source of Information and Perception of Insecurity - Cuenca, Mª Carmen Segura (European journal on criminal policy and research, 2025)
This study analyses the influence of social media as an information source on the perception of public insecurity, a phenomenon of growing relevance in the global context. Using data from the Seventh Wave of the World Values Survey (2017-2022), covering 66 countries, we assess the relationship between access to different information media and the perception of insecurity, while also considering sociodemographic and geographical factors. The methodology combined descriptive analyses, Chi-square tests, Kruskal-Wallis and Mann-Whitney U tests, a multilevel ordinal logistic regression model, and a decision tree model to identify key patterns. The results show that citizens who predominantly rely on social media for information tend to perceive higher levels of insecurity, with significant differences observed across regions and sociodemographic groups. Additionally, the analysis revealed non-linear associations between media consumption frequency and perceived insecurity, particularly with social media and traditional media such as newspapers and radio. These findings underscore the need for public policies aimed at regulating the quality of information on social media, in order to mitigate the spread of misinformation and its effects on security perceptions and social cohesion.